Food and social change: culinary elites, contested technologies, food movements and embodied social change in food practices : introduction - Campos Motta, Renata; Martín, Eloísa (The sociological review, 2021)
In this introduction, we have asked a very classical sociological question and brought together interdisciplinary efforts to critically approach it, focusing on a basic issue: food. We briefly reconstruct the main approaches to social change in sociological theory and then identify main themes with which food studies have contributed to this debate. If, to avoid normative and formal approaches, theories of change require contextualization in order to keep their explanatory value, this volume brings historical and geographical context to provide an analysis of social change through the lenses of food. Methodologically, articles offer diverse approaches to food, allowing different kinds of perspectives on change. While statistical analysis or historically comparative sociology will provide correlational snapshots and structural transformations, ethnographies necessarily deal with change happening in the everyday. The articles in this monograph have been organized into four broad groups: (1) national cuisines as elite projects of social change; (2) science and technology as contested tools for social change; (3) social mobilization and food movements as agents of social change; and (4) micro- and macro-level change and beyond: culinary subjectivities, embodied social change and food transition.
Gesehen am 27.03.2023